Professionalisation of Students with Disabilities into the Teaching Profession in South African Higher Education : Affordances and Challenges - Ndlovu, Sibonokuhle (African Higher Education: Developments and Perspectives, 2024)
To solve the global challenges of the present society, contemporary scholarship requires that all diverse social groups are included in knowledge production through education. Professionalisation is one way in which diverse social groups can engage in knowledge production in higher education. While all kinds of professionalisation produce citizens who can contribute to the social, political and economic development, the teaching profession is foundational as most people have come through the hands of teachers from basic to higher education. Teaching has been referred to as the noblest of professions because it does not only require acquisition of knowledge and skills, but high levels of professionalism, dignity, honour and the ability to lead by example. While inclusion of all diverse social groups is topical after attainment of independence in African countries largely and in South Africa particularly, professionalisation of students with disabilities into the teaching profession and in settings for integrated learning, has received little attention from scholars in the disability field. Professionalisation of Students with Disabilities into the Teaching Profession in South African Higher Education critically reflects on what affordances and challenges face students with disabilities in professionalisation into the teaching professions and on how students are socialised to identify with the profession. It does so from the lived experiences of students with disabilities, the academics who teach them, the support staff and the author's nuanced understanding of the professionalisation, the teaching profession, and transformation to include all in the South African context of higher education.